PENGARUH HARGA, PROMOSI, DAN KETIDAKPUASAN TERHADAP KEPUTUSAN PERPINDAHAN MEREK KE SIMCARD TELKOMSEL (Studi Pada Mahasiswa Kos Kelurahan Dinoyo Kota Malang) - Tarmizi Tarmizi; N. Rachma; M Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT This study aims to determine the effect of prices, promotions, and dissatisfaction with the decision to move the brand to the Telkomsel simcard in boarding students of Dinoyo Village, Malang City. The variables used in this study are brand switching variable as the dependent variable, while the independent variables are price and promotion, and the intervening variable is dissatisfaction. Data was collected through a questionnaire method with the number of samples used as respondents as many as 94 respondents. The results of this study are prices and promotions that have a direct effect on brand movements in Telkomsel cellular card consumers. Prices and promotions have a direct effect on dissatisfaction with Telkomsel cellular card consumers. Dissatisfaction has a direct effect on brand movement on Telkomsel cellular card consumers. Prices and promotions have an indirect effect on brand transfers to Telkomsel cellular card consumers. Keywords: brand switching, price, promotion, dissatisfaction